Clostridium difficile and inflammatory bowel disease. Issue 8 (August 1983) - Greenfield, C; Aguilar Ramirez, J R; Pounder, R E; Williams, T; Danvers, M; Marper, S R; Noone, P
Abstract : Stools from 109 patients with inflammatory bowel disease (13.4%) contained Clostridium difficile or its toxin, an incidence similar to the stools of 99 control patients with diarrhoea (11.9%), but significantly higher than the stools of 77 control patients with a normal bowel habit (1.4%). Sixty-six per cent of the diarrhoea controls, but only 11% of the inflammatory bowel disease patients, reported recent antibiotic use: however, 67% of inflammatory bowel disease patients were taking sulphasalazine. The presence of Cl difficile in the stool was not related to the clinical assessment of inflammatory bowel disease relapse, but it was related to hospital admission. During the one year study, 31 of the 109 patients (28%) with inflammatory bowel disease had one or more stool samples that were positive for Cl difficile.